CHINA’S AGRICULTURAL FOREIGN TRADE FLOWS: TRENDS, CHALLENGES, AND OPPORTUNITIES (ІННОВАЦІЙНА ЕКОНОМІКА, 2024)
Du W., Lishchynskyy I.O.CHINA’S AGRICULTURAL FOREIGN TRADE FLOWS: TRENDS, CHALLENGES, AND OPPORTUNITIESPurpose. The aim of the article is to analyse China’s agricultural import and export in the context of global geopolitical transformations and identification of trends, challenges, and opportunities for the state’s agricultural policy based on this analysis.Methodology of research. The following methods were used in the research: analysis and synthesis to evaluate the dynamics, product, and geographical structure of China’s agricultural foreign trade; SWOT analysis to assess the strengths, weaknesses, threats, and opportunities of the state’s agricultural policy; abstract and logical method to summarize information from various sources and create a comprehensive understanding of the researched problem, forming theoretical conclusions and generalizations; and graphical method to visualize the research results. Findings. It was found that in 2023, the dynamics of China’s foreign trade in agricultural products continued to show a growth trend that has been observed over the past decade. It was demonstrated that the development of China’s agricultural exports has effectively contributed to the deep expansion and diversification of the agricultural value chain, opening new opportunities for promoting high-quality agricultural development. At the same time, it was noted that China has abolished non-tariff measures on agricultural products and export subsidies for all agricultural products, making it one of the most open markets for agricultural products. However, it was proven that in terms of imports, China remains one of the most dependent countries in the world, which is related to the relatively small area of arable land, large population, and insufficient intensification, technological development, and mechanization of tangible agricultural production.Originality. The research on trends in the development of China’s international trade in agricultural products in the post-COVID period has been further developed, taking into account new geopolitical realities. Using the SWOT analysis method, the strengths, weaknesses, threats, and opportunities of China’s agricultural policy were identified.Practical value. The substantiated conclusions and recommendations derived from the research can be used to determine the strategic directions for the development of China’s trade relations, as well as to intensify agricultural trade flows between Ukraine and China.Key words: international trade, export, import, agriculture, peripheral regions, foreign policy, global risks, competitiveness. Ду В., Ліщинський І.О. СІЛЬСЬКОГОСПОДАРСЬКІ ЗОВНІШНЬОТОРГОВЕЛЬНІ ПОТОКИ КИТАЮ: ТРЕНДИ, РИЗИКИ ТА МОЖЛИВОСТІМета. Аналіз імпорту та експорту сільськогосподарської продукції Китаю в умовах глобальних геополітичних трансформацій та виявлення на цій основі тенденцій, викликів та можливостей для аграрної політики держави.Методи дослідження. У ході дослідження використано такі методи: аналізу та синтезу ‒ для оцінювання динаміки, продуктової та географічної структури зовнішньої торгівлі сільськогосподарською продукцією Китаю; SWOT-аналіз ‒ для оцінювання переваг, недоліків, загроз та можливостей аграрної політики держави; абстрактно-логічний – для узагальнення інформації з різних джерел і створення комплексного уявлення про досліджувану проблему, формування теоретичних висновків і узагальнень; графічний – для візуалізації результатів дослідження.Результати дослідження. Виявлено, що у 2023 році динаміка зовнішньої торгівлі Китаю сільськогосподарськими продуктами продемонструвала продовження тренду до зростання, що спостерігається протягом останнього десятиліття. Продемонстровано, що розвиток експорту сільськогосподарських продуктів Китаю ефективно сприяв глибокому розширенню та диверсифікації ланцюга доданої вартості в сільському господарстві, відкриваючи нові можливості для просування високоякісного розвитку сільського господарства. Водночас відзначено, що Китай скасував нетарифні заходи на сільськогосподарську продукцію та експортні субсидії на всі сільськогосподарські продукти, що зробило державу одним із найбільш відкритих ринків сільськогосподарської продукції. Разом із тим доведено,  що у випадку імпорту Китай залишається однією з найбільших залежних держав у світі, що пов’язано із відносно невеликою площею оброблюваних земель, великою чисельністю населення та недостатньою інтенсифікацією, технологічним розвитком та механізацією матеріального сільськогосподарського виробництва.Наукова новизна результатів дослідження. Дістало подальшого розвитку дослідження тенденцій розвитку міжнародної торгівлі сільськогосподарськими товарами Китаю у постковідний період з урахуванням нових геополітичних реалій. На основі методу SWOT-аналізу виявлено переваги, недоліки, загрози та можливості аграрної політики Китаю.Практична значущість результатів дослідження. Обґрунтовані за результатами дослідження висновки і пропозиції можуть бути використані при визначенні стратегічних векторів розвитку торгівельних відносин Китаю, а також для інтенсифікації торговельних сільськогосподарських потоків між Україною та Китаєм.Ключові слова: міжнародна торгівля, експорт, імпорт, сільське господарство, периферійні регіони, зовнішня політика, глобальні ризики, конкурентоспроможність.